Uma abordagem para auto identificação voluntária e verificável de participantes de aplicações baseadas em livros-razão distribuídos - Soares, Marcelo Hércules Cunha (2020)
Distributed ledger technologies have become popular through the advent of cryptocurrencies, especially Bitcoin, bringing new applicabilities and new challenges. Although they have been conceived in a financial context, associated to cryptocurrencies, it is currently easy to find such technologies being applied in several non-financial contexts. With the evolution of technology, there have been customizations with permission access control in private networks, where network participants are previously known. However, public DLTs can be considered safer because they have a large number of nodes composing networks, which makes fraud even more difficult. In the ecosystem of public DLTs, privacy and anonymity are desirable attributes for users. However, there is ample evidence that, in some cases, such attributes may be dispensable and the ownership of a digital wallet address must be known to ensure the legitimacy of a transaction. This work investigates the mechanisms of identification of participants in public DLTs, with the provision of a public address association service for entity, voluntarily fed by the address holder, called the Address Name System (ANS). The ANS combines the use of consolidated technologies, such as digital signature and certification, for the generation of an artifact, called ANS Certificate, which encryptively associates the holder of a digital wallet address with a real-world entity, and provides a architecture for the searching and validation of such certificates. As proof of the proposal’s concept, a prototype of the service was implemented and integration experiments were performed for the functional validation of its operations with real applications